Rear view of the Vishnu and Shiva temples behind the Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The rear view (northwest) of the Vishnu and Shiva temples behind the Sitaleshwar Temple shows that the temples are in disrepair. The ornately carved base mouldings of both temples are intact but the jangha (wall) and shikhara (superstructure) of both temples are severely damaged.